Application of molecular dynamics simulations in the study of protein-ligand interactions - Duan, Rui (2016)
Molecular dynamics (MD) simulation is a fundamental approach to allow researchers to study the molecular interactions of protein-ligand binding via the dynamics of protein-ligand complexes at atomic level. It can be observed precisely the motion of atoms and interactions involved in receptor and ligand binding using MD simulations. In this thesis, conventional MD simulations is applied to investigate the basis of mutation induced resistance HIV-1 integrase inhibitors, and positive agreement with experimental result has been observed and reasonable explanations are presented. Nevertheless, the deficiency of conventional molecular dynamics simulation is not negligible either. It lacks polarization effects in classical force fields utilized in traditional MD simulations, consequently the capability of describing the specific electrostatic properties of different biological systems is absent. Previously developed polarized protein-specific charge (PPC) allows electrostatic polarization effect to be introduced into molecular dynamics simulation as static charges. In this thesis, this method is employed in MD simulations to explore the mechanism of governing resistance to its inhibitor while HIV-1 protease Ile mutates to Val at position 50 in both chains; and the importance of electrostatic polarization effect and advantages compare to classical force field is demonstrated. The result shows polarization effect included simulations are more reliable comparing with experimental data. However, static PPC charges are calculated based on single conformation, and it causes bias of atomic charges, e.g. overestimate particular hydrogen bond strength resulting extra stability during simulation. As conformations of the systems varying dynamically would lead to electrostatic environment change, atomic charges in system should also be re-calculated during MD simulations. Environmentally corresponding local polarized protein-specific charge (ECLPPC) scheme and environmentally corresponding hydrogen bond dependent polarized protein-specific charge (ECHBPPC) scheme have been newly developed and applied in protein-ligand MD simulations. They update the atomic charges of ligand and selected residues in certain criteria surrounding the ligand periodically to incorporate polarization into MD simulations. MD simulations are conducted by employing ECLPPC and ECHBPPC respectively to investigate the basis of avidin-biotin interaction and give reasonable results with agreement to experiment.